2019
DOI: 10.1111/jfbc.12835
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two types of vinegar with different aging times by NMR‐based metabolomic approach

Abstract: Shanxi vinegar (SV) is well known as the most famous vinegar for its distinctive processing technique in China. Aging is the most important process for SV, and we call the vinegar aging more than 1‐year Shanxi aged vinegar (SAV) and less than 1‐year Shanxi mature vinegar (SMV). In this study, the chemical compositions and in vivo difference between SAV and SMV were compared by NMR based metabolomic profiling technique and multivariate statistical analysis. The results indicated that most of the metabolites exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Traditional Chinese vinegars are mostly brewed through multi-strain mixed fermentation in an open environment using cereals as raw material. However, different vinegars have distinct characteristics depending on the various flavor substances present ( Nie et al, 2019 ), and because of their different raw materials, climates, regions, and microbial community structures ( Al-Dalali et al, 2019 ; Zhang et al, 2019 ). Furthermore, some vinegars must be brewed in a multi-step process, and the various steps have a significant impact on flavor ( Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese vinegars are mostly brewed through multi-strain mixed fermentation in an open environment using cereals as raw material. However, different vinegars have distinct characteristics depending on the various flavor substances present ( Nie et al, 2019 ), and because of their different raw materials, climates, regions, and microbial community structures ( Al-Dalali et al, 2019 ; Zhang et al, 2019 ). Furthermore, some vinegars must be brewed in a multi-step process, and the various steps have a significant impact on flavor ( Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aroma profiling of Chinese vinegars using GC/MS and GC-O suggested that volatile compounds are enriched during vinegar aging [ 10 ]. Similarly, an NMR-based metabolomic study reported that the concentrations of most vinegar metabolites increased after aging longer than a year [ 20 ]. Because TVs undergo alcoholic fermentation and require longer fermentation and aging periods, compounds that are significantly more abundant in TVs would be closely associated with fermentation processes.…”
Section: Resultsmentioning
confidence: 99%
“…Vinegar aging is crucial to organoleptic quality despite differences in production methods. Aging involves chemical reactions, evaporation, ester formations, and interactions with wood, which improves the integration of aromas and metabolites [8,10,30,[133][134][135][136].…”
Section: Vinegar Production: From Fermentation To Qualitymentioning
confidence: 99%
“…These reactions result from residual microorganisms, enzymes, and interactions with the oxygen introduced during fermentation. Over time, these reactions form new compounds, contributing to the richness and complexity of the vinegar's flavor profile [10,30,133,135]. Evaporation during aging is a noteworthy phenomenon.…”
Section: Vinegar Production: From Fermentation To Qualitymentioning
confidence: 99%